Inițiative antreprenoriale în domeniul comerțului electronic de produse specifice industriilor creative - Leovaridis, Cristina; Gheorghe, Mihai-Adrian (Calitatea Vieții, 2021)
The present paper intends to identify the main features of Romanian small entreprises entrepreneurs in online commerce of some of the creative industry branches. Also, the main characteristics of their businesses, in their view, and in the view of several experts in the field, are going to be described. E-commerce allowed these firms to break some barriers which were obliterating their development, offering opportunities to enter new markets, and to eliminate some additional unnecessary costs. After a theoretical view and a statistical analysis of Romania`s small firms situation, in an European perspective, and the depiction of some of the concepts in the field (entrepreneurship, small firms, creative industries, online commerce), the paper further focuses on the applicable/ practical side of the domain, based on a qualitative research using several interviews with entrepreneurs and experts in the studied field.